Kajian Hukum Terhadap Perlindungan Lingkungan Pantai Dari Kegiatan Wisata di Labuan Bajo - Fristikawati, Yanti; Adipradana, Nugroho (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Labuan Bajo is one of the super priority tourism destinations that has been planned by the Indonesian Government because of the presence of rare Komodo animals and also its natural beauty. To support this goal, various efforts have been made to increase the number of tourist visits, including by providing adequate hotel facilities and restaurants and other tourist facilities. In reality, tourism activities in Labuan Bajo cause environmental damage that threatens the Komodo habitat and damages the coastal and marine environment. How are the regulations regarding the environment, especially from tourism activities, including criminal sanctions that can be applied to perpetrators of violations? This study was conducted descriptively, namely collecting existing regulations, both regulations regarding the environment and tourism, and also observing tourism activities in Labuan Bajo directly for analysis. The results of the study show that existing regulations are quite adequate, but there are still violations committed by tourism business actors